Life on the Slippery Slope: A Bedside View of Treating Incompetent Elderly Patients - Niemira, Denise (The Hastings Center report, 1993)
Physicians are practicing in an age of cognitive dissonance, doing much for fragile elderly patients in the short run, even if there is little they can do in the long run. In such a setting, how can one determine what counts as good care?